2023
DOI: 10.2196/43116
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Pornography and Adolescent Sexual Behavior: Systematic Review

Abstract: Background Formative experiences in adolescence lay the foundation for healthy and pleasurable romantic and sexual relationships. Exposure to pornography may affect these experiences. Objective We aimed to synthesize evidence published in the past decade on the relationship between exposure to pornography and sexual behavior (earlier age of first sex [<16 years], condomless sex, past-year multiple partners [>1], lifetime multiple partners [>1],… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…On this point, the literature indicates that early sexual experience among adolescents occurs in the context of sexual coercion and violence [1, 13, 67]. This study also revealed that a high frequency of watching pornographic films was associated with penetrative sexual experience, which is consistent with previous studies indicating that exposure to pornography may have harmful effects on sexual maturation and behaviours in adolescents [17, 68, 69] and that first sex was associated with exposure to pornography [7072]. In addition, another study involving adolescents aged 10-19 years in rural eastern Uganda found that watching sexually explicit films was associated with ever having sexual intercourse [73].…”
Section: Discussionsupporting
confidence: 90%
“…On this point, the literature indicates that early sexual experience among adolescents occurs in the context of sexual coercion and violence [1, 13, 67]. This study also revealed that a high frequency of watching pornographic films was associated with penetrative sexual experience, which is consistent with previous studies indicating that exposure to pornography may have harmful effects on sexual maturation and behaviours in adolescents [17, 68, 69] and that first sex was associated with exposure to pornography [7072]. In addition, another study involving adolescents aged 10-19 years in rural eastern Uganda found that watching sexually explicit films was associated with ever having sexual intercourse [73].…”
Section: Discussionsupporting
confidence: 90%
“…In general, previous research focuses on the negaYve aspects of pornography use, but some research notes that, in certain circumstances, pornography can provide useful informaYon about sex (Litsou et al, 2021). For LGBTQ+ young people in parYcular, online pornography can allow for exploraYon without the social sYgma that can occur in offline selngs (Litsou et al, 2021;Luder et al, 2011;Pathmendra et al, 2023;Peterson et al, 2023). This hypothesis is supported by the findings of See also the roll-out of the Active* Consent Programme; see https://www.gov.ie/en/press-release/1ed9f-activeconsent-programme See https://www.sexualwellbeing.ie/for-parents this research, where young people from LGBTQ+ groups, especially women, were significantly more likely to use online pornography.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…Pa]erns of behaviour that develop in adolescence and young adulthood shape outcomes throughout the life course (Viner et al, 2015). Curiosity and experimentaYon are common in the context of adolescent development, and adolescents who experience healthy relaYonships are more likely to have healthy relaYonships in their young adulthood (Pathmendra et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All countries are concerned, and regulations in India have passed to protect teenagers, and porn sites have been banned [5]. However, few studies consider that pornography could be used for triggering sexual education of teenagers who could talk about sexual behaviors to parents or adults at home or at school [6,7]. Unfortunately, a future of love seems to be the development of robots [8].…”
Section: Introductionmentioning
confidence: 99%